Perkembangan Masyarakat Islam di Spanyol Pada Masa Keamiran (755-912 M) - Muhammad Nurhidayat Bahmi; Hafsah Hafsah; Soraya Rasyid; Aksa Aksa; Syamsiah Syamsiah; Nuraeni S Nuraeni S (Tarikh : Journal of Islamic History and Civilization, 2026)
This article reveals the role of Islamic civilization in early Spain, which is often overlooked in the narrative of Modern European history, and to show its contribution to the intellectual revival of Europe. Meanwhile, the goal is to analyze the development of Muslims in Spain from their initial arrival until the formation of the emirate government system, especially during the emirate period in Cordoba (755-912 AD). The method used in this article is the library research method with a historical approach that includes heuristics, source criticism, interpretation, and historiography. The results of the study show that the arrival of Muslims was not solely to control the region, but to overthrow King Roderick of the Visigoth Kingdom, and spread the teachings of Islam in harmony. Not to forget the progress of science, the progress of magnificent architectural buildings, which could rival the Abbasid Caliphate and became the starting point of the European revival. The novelty of this article lies in the emphasis that the transformation of Andalusia into a center of knowledge occurred during the emirate phase, not only in the early period of the caliphate. The implications for policy on the integration of Spanish Muslim scholarship into the curriculum of history education and global civilization studies, in order to provide a foundation of knowledge for future generations to apply in the modern era.